Etsi Deus non daretur. Quale uso nel discorso pedagogico? - Mattei, Francesco (Studi sulla Formazione/Open Journal of Education, 2012)
The Grozio’s sentence “etsi Deus non daretur” has many interpretations: studying the relationship between faith and reason, between religiosity and laicism, etc., is necessary to question why the occidental culture excludes God from public consciousness. Beyond the indoctrination, the text hopes epistemological analysis – able to master the rules of speech and the logic of language – about the presence of God in the pedagogical discourse.